Analisis Kesediaan Konsumen Membayar Durian di Gerai Ucok Durian Medan: Analysis of Consumer’ Willingness to Pay for Durian at Ucok Durian Medan Outlet - Chintia Damayani P; Titik Ekowati; Edy Prasetyo (Universitas Widya Gama Mahakam, 2021)
Durian is a plant that isn’t always available at all times or called local durian. This condition encourages Ucok Durian outlets to always provide good quality durian. This study aims to describe the characteristic of consumers durian, analyze the average value of maximum that consumers are willing to pay, and determine the factors that influence consumers’ Willingness To Pay (WTP). The research method is the survey method, conducted at the Ucok Durian Medan outlet. The sampling method used accidental purposive sampling and the determination number of samples using quota sampling of 80 respondents. Data analysis used descriptive analysis to explain consumer characteristics, Contingent Valuation Method (CVM) analysis to calculate the value consumers WTP for durian, and logistic regression analysis to analyze the factors that influence consumers’ WTP for durian. The results showed that most of the consumers is male (72.6%), 17-25 years old (38.8%), married status (73.8%), last education is Diploma and S1 (56.2%),the number of family members is 4-6 people (65%), formal work (91.2%) and income> Rp 4,000,000 - Rp 7,000.000/month (38.8%). As many as 86.25% of respondents are willing to pay for durian which is more expensive than the normal price. The average value of the consumer's WTP for durian, respectively, is Rp 50,000 and Rp 75,000, amounting to Rp 53,284.31 and Rp 75,625/piece, with a proportion of 6.57% and 0.83% of the current price. The factors that influence consumers’ WTP for durian are jobs, price, product quality, and lifestyle.